TOPICAL BACTERIAL LYSATES IN PEDIATRIC CHRONIC TONSILLITIS TREATMENT - М.М. Polunin; L.S. Titarova ("Paediatrician" Publishers LLC, 2011)
Chronic tonsillitis remains a current problem in pediatric health due to the risk of nonspecific systemic heart, renal and joint diseases. High social significance and prevalence among children call for effective preventive and treatment measures against this disease. Topical bacterial lysates recently have become popular among physicians as safe and effective component of tonsillitis treatment. Key words: chronical tonsillitis, childhood, bacterial lysates. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 176-178)